Prevention and Control Measures for Imported SARS-CoV-2 Transmission During the Postpandemic Period in Shenzhen, China. (4th March 2023) - He, Xuru; Gong, Fangfang; Sun, Xizhuo; Hu, Guangyu; Lin, Jinchun
Abstract: In China, most cities have gradually controlled the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and brought coronavirus disease 2019 (COVID-19) under control locally. This means that crucial work has shifted from internal management of the pandemic to external prevention and control, especially management of international travelers and imported goods. There is much uncertainty about variants of concern for SARS-CoV-2, which pose challenges to the steady resumption of social and economic life once the mutant strains begin to spread. The sporadic outbreaks of COVID-19 in different provinces of China caused by these mutant strains emphasizes the need for both prevention and control measures. Therefore, we introduce China's experience with preventing and controlling COVID-19 in the postpandemic period, which may serve as a reference in various settings.